1) Simplify the left side of the equation: -6(x + 3) + x = -6x + 30
2) Distribute -6: -6x - 18 + x = -6x + 30
3) Combine like terms: -6x + x -18 = -6x + 30
4) Combine like terms: -5x - 18 = -6x + 30
5) Add 5x to both sides: -18 = -x + 30
6) Subtract 30 from both sides: -48 = -x
7) Multiply both sides by -1: 48 = x
8) Simplify: x = 48
Order the the steps to solve the equation for x. Make sure to put the steps in order. Not all steps will be used.
-6(x + 3) +x = -6x + 30
x = 12
-6x -18 + 4x = -6 x + 30
4x - 18 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8
x = 12
-6x -18 + 4x = -6 x + 30
-6x +3 + 4x = -6x + 30
4x - 18 = 30
-8x + 3 = 30
-2x -18 = -6x + 30
4x = 48
-8x = 27
x = -27/8
1 answer